IMPLEMENTATION OF THE SLUM-HOUSING UPGRADING PROGRAM IN BANDAR LAMPUNG IN 2014 - Department, administratio; Astuti, Sri Puji; Hermawan, Dedy; Sulistiowati, Rahayu (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2018)
ABSTRACT. The Slum-Housing Upgrading Program is an effort to accelerate poverty alleviation in Bandar Lampung. The aim of the program is to support poor families in order to have decent houses so that they are able to fulfil their basic needs. The purpose of this study was to examine the implementation of the slum upgrading policy in Bandar Lampung in 2014, and to investigatethe factors that hindered the implementation. The method used in the study was a descriptive qualitative approach. The data wereobtained through interviews, observation and documentation. The results showed that (1) socialization process or information delivery has been conducted at the program executive level, however, the information dissemination to the targeted groups have not beenproperly implemented. (2) There are a limited number of human resources as the executor of the program and limited funding resources. (3) The tendency to implement the policy by the stakeholders in supporting the slum-upgrading program has been perceived as sufficient (4) Inthepolicy implementation, the basic work procedures or the standard operating procedures of the slum-upgrading program have been available as a standard or reference used by the policy implementers during the slum-upgrading policy implementation, the tasks division among organizationunits have been well conducted and coordinated. Furthermore, there exist somethreats that trigger problems in the program implementation which are house/land ownership status, data accuracy and objectivity of targeting, the limited budget, and lack ofstaff for field work. The research recommends that: (1) the information dissemination needs to be further boosted(2) the recruitment of staff needs to fit the requirement of the organization (3) the commitment to the slum-upgrading policy needs to be enhanced (4) the coordination needs to be further improved. Keywords: Policy Implementation, Poverty Alleviation.